Indikasi Penyimpangan dalam Penafsiran Al-Qur’an - Sulaiman Ibrahim (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This paper aims to analyze indications of irregularities in interpreting the Koran. The method used is a literature review with a discourse analysis approach. This paper shows that every result of a person's thoughts is influenced not only by the level of intelligence, but also by the scientific disciplines practiced, both through experience, scientific discoveries, social conditions, politics, and so on. This also causes a different mufasir in interpreting the Qur'an. This shows that there are two factors that lead to indications of deviations in the interpretation of the Qur'an, namely: the tendency of the interpreter to believe in the meaning without looking at the explanations contained in the recitations of the Koran, and the tendency of the interpreter to simply paying attention to the pronunciation and meaning that can only be understood by speakers of Arabic, without paying attention to what is actually desired by those who speak the Qur'an.